2003
DOI: 10.1084/jem.20022218
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin D2 Reinforces Th2 Type Inflammatory Responses of Airways to Low-dose Antigen through Bronchial Expression of Macrophage-derived Chemokine

Abstract: PGD2, a lipid mediator released from mast cells, is known to participate in allergic reactions. However, the mechanism by which PGD2 contributes to such reactions remains unclear. We established a novel experimental model of asthma that permitted direct assessment of the role of PGD2 in airway inflammation. Antigen-sensitized mice were exposed to aerosolized prostaglandin D2 (PGD2) 1 d before challenge with low-dose aerosolized antigen. Not only the numbers of eosinophils, lymphocytes, and macrophages but also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
83
2
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(92 citation statements)
references
References 69 publications
4
83
2
3
Order By: Relevance
“…Interestingly, PGD 2 and its high affinity receptors DP1 and CRTH2 (chemoattractant-homologous receptor expressed on Th2 cells) have been shown to be crucial for the promotion and maintenance of allergic responses (51)(52)(53)(54)(55). Importantly, although PGD 2 promotes inflammatory responses through its CRTH2 receptor, which is selectively expressed on eosinophils, Th2 T cells, and basophils (54,55), PGD 2 also has anti-inflammatory and inhibitory effects on neutrophils (56,57). Therefore, it is possible that TSG-6 contributes to the induction of robust allergic inflammation and AHR through promoting the production of PGD 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, PGD 2 and its high affinity receptors DP1 and CRTH2 (chemoattractant-homologous receptor expressed on Th2 cells) have been shown to be crucial for the promotion and maintenance of allergic responses (51)(52)(53)(54)(55). Importantly, although PGD 2 promotes inflammatory responses through its CRTH2 receptor, which is selectively expressed on eosinophils, Th2 T cells, and basophils (54,55), PGD 2 also has anti-inflammatory and inhibitory effects on neutrophils (56,57). Therefore, it is possible that TSG-6 contributes to the induction of robust allergic inflammation and AHR through promoting the production of PGD 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Prostaglandin D 2 (PGD 2 ) is a well known inflammatory mediator in peripheral tissues (Matsuoka et al, 2000;Honda et al, 2003;Kabashima and Narumiya, 2003), invoking airway inflammation (Matsuoka et al, 2000;Shiraishi et al, 2005), inhibiting platelet aggregation (Yun et al, 1991), and causing peripheral vasodilatation (Soter et al, 1983;Alving et al, 1991). PGD 2 is synthesized by hematopoietic PGD synthase (HPGDS) and lipocalin-type PGDS (L-PGDS) and exerts its actions by binding to specific receptors, DP 1 or DP 2 (Kabashima and Narumiya, 2003;Nagata and Hirai, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…We have reported that COX-2 inhibitors, which stop the synthesis of PGD 2 in the lungs of allergen-sensitized and exposed guinea pigs, attenuated the accumulation of eosinophil in the airways (19). Others have reported that the overexpression of PGD synthase or inhalation of aerosolized PGD 2 enhanced the allergen-induced airway eosinophilia in mice (20,21).…”
mentioning
confidence: 96%